SMALL AND MEDIUM ENTERPRISES AS FACTORS IN REDUCING POVERTY IN RURAL COMMUNITIES SERBIAN - Maletić, Radojka; Ceranić, Slobodan; Popović, Blaženka (Economics of Agriculture, 2011)
Inclusion of rural population into social trends and development processes is og key importance for Serbia, considering that rural regions make 85% of its territory, participating in the gross national product with 41%, and rural population makes 42% of total population. Inclusion of rural population is important at the same time from the persepctive of quality of life, realization of rights and development of the potential of rural population, as well as from the aspect of sustainable development of rural communities. Rural labour market in Serbia was devestated during transition, which as a consequence had dislocation of surpluses of industrial labour into sector of agriculture and increase of hidden unemployment and poverty on holdings. Therefore, in this paper, some of the facts which could considerably mitigate current poverty situation in Serbia are presented.